Service Quality Delivery through Web Sites: A Critical Review of Extant Knowledge - Zeithaml, V. A.; Parasuraman, A.; Malhotra, A. (Journal of the Academy of Marketing Science, 2002)
Evidence exists that service quality delivery through Web sites is an essential strategy to success, possibly more important than low price and Web presence. To deliver superior service quality, managers of companies with Web presences must first understand how customers perceive and evaluate online customer service. Information on this topic is beginning to emerge from both academic and practitioner sources, but this information has not yet been examined as a whole. The goals of this article are to review and synthesize the literature about service quality delivery through Web sites, describe what is known about the topic, and develop an agenda for needed research.